The Customer's Main Considerations in Choosing an Educational Institution Viewed from the Elements of the Marketing Mix at Amanatollah Gambiran Junior High School Banyuwangi - Arifin, Samsul (LAN TABUR : Jurnal Ekonomi Syariah, 2022)
The purpose of this study is to describe the customer's main considerations in choosing an educational institution in terms of the marketing mix elements at Amantollah Junior High School Gambiran Banyuwangi. This research method uses a descriptive qualitative approach. The results of the research show: 1) the products/programs provided by SMP Amantollah Gambiran to customers are institutions based on Islamic boarding schools, tahfidz programs, studying general science and religion and shaping the character of students with good morals; 2) physical evidence or facilities and infrastructure for junior high schools are complete and in demand by educator customers so that they get satisfaction; and 3) a price of IDR 500,000 determined by the foundation can be of interest to educators' customers because it is affordable and attractive to all members of the community.